If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + 6x) = 48 (4 * 3 + 6x * 3) = 48 (12 + 18x) = 48 Solving 12 + 18x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 18x = 48 + -12 Combine like terms: 12 + -12 = 0 0 + 18x = 48 + -12 18x = 48 + -12 Combine like terms: 48 + -12 = 36 18x = 36 Divide each side by '18'. x = 2 Simplifying x = 2
| a+5-2a= | | -4(5x-10)=40 | | 9a+2b=766.97 | | 4x+5=8x-31 | | 3y-y=-5+30 | | 17-2x=x+8 | | 34=3(w-2)-7w | | 6(3x+6)=-180 | | -0.2+x=1.4 | | 16x^4-a^4=0 | | 17-2x+x=8 | | 23g+1=19 | | 5+-10*2= | | (16x-2)=(8x+14) | | T(n)=3n+1 | | -3(5p+2)-2(3-17p)=3(6+6p) | | 3+5x=-3x-93 | | 20x+7y=3fory | | 8m-24=4 | | 6x+5=-3x+104 | | -5x+4=68+3x | | -2x+10+7x=65 | | 4+7x+x=68 | | 180=(30+x)+30+9x | | 8.5+x=7.1-x | | 62=y-19 | | x^4-8x^3+24x^2-32x=65 | | 15y-9y= | | -3-y=6 | | (40x)+(100y)=2500000 | | 2x+9=13+2x | | 15-2y/4=3 |